Integrated Satellite-Terrestrial Communication Systems:Architectures, Enabling Technologies and Prototype Verification - Rui DING; Tianhao FANG; Wenjin WANG; Yu LIU; Wei MA; Yi WAN (天地一体化信息网络)
The integrated satellite-terrestrial communication system is considered one of the development trends of future communication systems for its ability to provide seamless coverage and service.However, the differences between satellite and terrestrial communication networks, e.g., large propagation delays, large Doppler shifts, and large cell radius, pose challenges to fulfilling integrated satellite-terrestrial communication systems.The network architectures and key enabling technologies were discussed and analyzed and a prototype system for the terrestrial verification of integrated satellite-terrestrial communication systems was proposed.